THE IMPACT OF ELECTRICITY, CO₂ EMISSIONS, AND FOSSIL ENERGY ON INDONESIA'S ECONOMIC GROWTH - Nazla Salsabila; Jariah Abubakar (RADJA PUBLIKA, 2025)
This study aims to analyze Electrical Energy, CO2 Emissions and Fossil Energy on Economic Growth in Indonesia. This study uses secondary data from 1980-2023 obtained from the Central Statistics Agency. The data analysis method is the Autoregressive Distributed Lag. The results of the study show that in the short term, electrical energy shows a significant negative effect on economic growth. While CO2 emissions and fossil energy show a significant positive effect on economic growth. In the long term, electrical energy, CO2 emissions and fossil energy do not show a significant effect on economic growth.